States of intoxication - O'Brien, John, author.
1 online resource (202 pages).
Keywords: This book provides an illuminating perspective on alcohol use, drawing on approaches from both anthropological research and historical sociology to examine our ambivalent attitudes to alcohol in the modern West. From anthropological research on non-Western, non-modern cultures, the author demonstrates that the use of alcohol or other psychoactive substances is a universal across human societies, and indeed, has tended to be seen as unproblematic, or even a sacred aspect of culture, often used in a highly ritualised context. From historical sociology, it is shown that alcohol has also been central to the process of state formation, not only as a crucial source of revenue, but also through having an important role in the formation of political communities, which frequently are a source of existential fear for ruling groups. Tracing this contradictory position occupied by alcohol over the course of history and civilisation, States of Intoxication sheds light on the manner in which it has produced the very peculiar modern perspective on alcohol.